The Use of Control Group in the Sports Science Research: The Ethical Challenge - Gonçalo Louro; Ricardo Ferraz; Pedro Forte; José E. Teixeira; Luís Branquinho; Dulce Esteves (Desafio Singular, 2023)
Medical ethicists have questioned the use of no-treatment controlled studies (placebo and sham procedure) of new therapies when safe and effective standard therapies are available for use as an active or "equivalence" control. Currently, ethical and conduct principles for biomedical research specifically prohibit projects that do not make or deny the "best-proven diagnosis and therapeutic treatment" to any participant in a clinical trial, including individuals who consent to randomisation into a control group. Studies of psychophysiological therapies are often criticised for not having a placebo or sham treatment control group. In sports science research, particularly in the case of clinical exercise, the use of control groups also raises ethical questions. This article briefly reviews the problem and discusses the ethical standards governing human research derived from the Nuremberg Code and the Declaration of Helsinki.